Cavities in Law Regarding Consumer Protection Due to Non-Similar Trademark Similarities - Apriyani, Ida; Sejati, Hono; Amin Zaini, Naya (Devotion : Journal of Research and Community Service, 2024)
Consumer protection is an important aspect of intellectual property law, particularly in the context of non-similar trademark similarities. This study aims to identify legal gaps that arise due to the lack of clear regulations concerning trademarks that are not of the same type. In this research, the research method used is the statutory approach, also known as normative legal research. In the first subsection, various forms of legal gaps are outlined, including difficulties in determining the level of similarity between trademarks in different categories and the impact this has on consumers' rights to receive quality products. This study also discusses the consequences arising from these legal gaps, such as confusion among consumers and the potential for deception by irresponsible business actors. Additionally, the study suggests remedial measures, including the need for regulatory revisions and strengthening law enforcement, to ensure more effective protection for consumers. It is hoped that the results of this research can contribute to the development of better legal policies for consumer and trademark protection in Indonesia.